Optical properties of silicon-implanted polycrystalline diamond membranes. (15th April 2021) - Kambalathmana, H.; Flatae, A.M.; Hunold, L.; Sledz, F.; Müller, J.; Hepp, M.; Schmuki, P.; Killian, M.S.; Lagomarsino, S.; Gelli, N.; Sciortino, S.; Giuntini, L.; et al.
Abstract: We investigate the optical properties of polycrystalline diamond membranes containing silicon-vacancy (SiV) color centers in combination with other nano-analytical techniques. We analyze the correlation between the Raman signal, the SiV emission, and the background luminescence in the crystalline grains and in the grain boundaries, identifying conditions for the addressability of single SiV centers. Moreover, we perform a scanning transmission electron microscopy (STEM) analysis, which associates the microscopic structure of the membranes and the evolution of the diamond crystals along the growth direction with the photoluminescence properties, as well as a time-of-flight secondary ion mass spectrometry (ToF-SIMS) to address the distribution of Si in implanted and un-implanted membranes. The results of the STEM and ToF-SIMS studies are consistent with the outcome of the optical measurements and provide useful insight into the preparation of polycrystalline samples for quantum nano-optics. Graphical abstract: Image 1